Electrochemical sensor based on Sb nanoparticles/reduced graphene oxide for heavy metal determination - Silva, Martin K. L. [UNESP]; Cesarino, Ivana [UNESP] (Taylor & Francis, 2020)
This paper presents the characterisation and for the first time the application of a nanocomposite based on reduced graphene oxide (rGO) modified with antimony nanoparticles (SbNPs) in the stripping analysis of Cd2+, Pb2+, Cu2+ and Hg2+ in natural water samples. The nanocomposite was easily synthesised by a chemical reduction approach using sodium borohydride as the reductant agent. The designed experiment investigated the remarkable rGO electronic properties with the synergetic combination of metallic SbNPs. The results showed that the GC/rGO-SbNPs electrode selective detected the heavy metal ions (HMIs) with suitable sensitivity. Under optimal conditions, the proposed electrode showed a good linear relationship with the concentration of Cd2+, Pb2+, Cu2+ and Hg2+ ranging from 0.1 to 4.5 µmol L−1 with detection limits for simultaneous determination of 45.3, 16.5, 34.1 and 4.8 nmol L−1, respectively. This presented work enables a full understanding of rGO-SbNPs properties in stripping analysis of HMIs, as well as a novel approach for future in situ analysis.
Keywords: antimony nanoparticles; electrochemical sensor; Graphene; heavy metal ions